Sunday Pictorial, 9 May 1926 (page 1)
1926-05-09 1918-1939 "Sunday Pictorial, 9 May 1926 (page 1)" [g0844001.jpg], 9 May 1926, Sunday Pictorial Almost every London newspaper printed some sort of edition with the help of volunteer labour. For the first few days, these were often single type written sheets, but by the weekend they had settled into regular formats with photographs. Outside of London, the newspapers returned to normal size editions even more quickly and others such as the 'Scotsman', were produced by non-union labour and were unaffected. The Nine Days